Synthesis of Graphene Oxide Enriched Natural Kaolinite Clay and Its Application For Biodiesel Production - Syukri Syukri; Fadhil Ferdian; Yetria Rilda; Yulia Eka Putri; Mai Efdi; Upita Septiani (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
A heterogeneous catalyst is one type of catalyst which is very effective for biodiesel production; thus, in this study, a novel heterogeneous bifunctional catalyst was prepared by kaolinite clay obtained from Padang of West Sumatera and impregnated with graphene oxide and potassium hydroxide (KOH) for the simultaneous esterification and transesterification reactions of palm oil into biodiesel. For comparison, two other catalysts were also prepared. The first catalyst was the same clay which was heated at 450ºC for 4 hours, and the second catalyst was the same clay which was impregnated with potassium hydroxide (KOH) only. The three catalysts were characterized using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), and Fourier Transform Infra-Red (FTIR). XRF analysis showed that the clay sample’s main composition consisted of 54% silica, 35% alumina, and 7% hematite. The XRD analysis results showed that the most dominant crystal composition was quartz, kaolinite, and hematite. The analysis results using FTIR showed a change in intensity and shift in wave numbers indicating a cation exchange. The catalytic activity test was carried out with a ratio of oil and methanol 1:6, catalyst amount 5%, 60ºC reaction temperature, and 4 hours of reaction time.The results showed that the catalytic activity of clays impregnated with graphene oxide and potassium hydroxide was better with a yield of 58% compared to clays without impregnation and other clays that were only impregnated with KOH under the yields of 0.8% and 0.4%, respectively